Achievement of sustainable environment through effectiveness of social media in Z generation of China - Chen, Bing; Madni, Ghulam Rasool (PloS one, 2023)
Social media is emerged as a powerful communication tool over the past ten years. The Z generation’s green buying habits and purchase intentions are being reshaped by social media, which is helping to advance the development of a sustainable environment. The consumption of non-organic products has raised carbon emissions, so changing consumption patterns and purchase intentions is necessary for a more sustainable future. Moreover, earlier literature has the absence of a comprehensive behavior change model that explains the mechanism through which social media influences sustainable behaviors This study explores that how social media affects patterns of consumption for Z generation of China while considering the role of environmental concerns, subjective norms, eco-branding and eco-labeling on the basis of theory of planned behavior. A questionnaire is used to get information from the 563 Z generation respondents of China. The data is analyzed using Smart-PLS and empirical outcomes show that social media has a statistically significant influence on shaping and affecting green consumption behavior of China’s Z generation because it has the potential to reach a vast audience and spread awareness about environmental issues, leading to increased intention towards a sustainable environment and reduction in carbon emissions. It also provides a platform for individuals to express their opinions and engage in discussions on environmental issues. These developments are promising for the future of environmental sustainability as they indicate a growing interest in preserving the planet among the Z generation of China. It can be recommended as a policy tool that government and other organizations should support the development of informative content on social media platforms, highlighting the importance of environmental sustainability and eco-friendly habits.